Preterm Birth: A Review - Schellenberg, Jean-Claude (Current Women's Health Reviews, 2006)
Preterm birth at less than 37 weeks gestation is a substantial burden to the community, representing a major source of infant death, severe handicap, and suffering for both victims and their families. Despite considerable research, little progress has been made in its prevention, partly because preterm birth is the endpoint of a silent multifactorial syndrome which begins long before labour starts. Infectious inflammation often plays a central role, but maternal susceptibility is probably also critical. Although progestogen treatment is preventive in some women with a prior history of preterm birth this will have little impact on the overall preterm birth rate unless effective treatment can be used in a much larger population of at risk women. An accurate screening test to identify such women is needed. The discovery of a screening test and of novel treatments requires a better understanding of the underlying biomolecular events. This paper gives an overview of the physiology and molecular biology of normal and abnormal pregnancy and parturition, the causes and consequences of preterm birth, and the difficulties of predicting and preventing preterm birth.
Keywords: diagnostic test